Caracterização de isolados de Xanthomonas axonopodis pv. manihotis por análise de isoenzimas e agressividade - Portz, Roberto Luis (2003)
The bacterial blight of cassava (Xanthomonas axonopodis pv. manihotis) is the most important disease in the culture of the cassava and its occurrence is generalized in all the places where it is cultivated. The intensity of the disease is related, mainly, with the resistance and age of the plant and with the soil and weather conditions. With the objective of obtaining information about the genetic variability of these bacteria in the West region of Paraná, a research was accomplished, throughout sampling of stems with similar symptoms to the caused by the disease, at Entre Rios do Oeste, Marechal Cândido Rondon, Mercedes, Missal, Nova Santa Rosa and Pato Bragado. Stems of cassava varieties destined for industry and varieties for human consume were sampled. The isolates obtained were characterized to "in vitro" amylase activity, eletrophoretic analysis of isoenzymes α and β-esterase and aggressiveness. From 61 collected materials, it was possible to obtain 19 isolated of X. axonopodis pv. manihotis. Materials of human consume varieties showed larger incidence than those for industry. Stems from Pato Bragado, Entre Rios do Oeste and Mercedes showed incidences of 10, 27 and 10%, respectively, values smaller than those of Marechal Cândido Rondon (50%) and Nova Santa Rosa (58%). The isolates could be contained in three, six and 12 different groups to amylolytic activity, aggressiveness and esterase isoenzimes, respectively. There was not relationship between the amylase activity and aggressiveness of the isolates. Based on the origin, isolates of Marechal Cândido Rondon were more aggressive than those of other sampled areas. The clustering for esterase allowed to verify that isolates from Entre Rios do Oeste, Nova Santa Rosa and Mercedes showed high similarity degree. These results indicate there to be differentiation among the isolates of the bacteria presents in the studied regions